2012
DOI: 10.1029/2011jb008545
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric and upper mantle structure of the northeastern Tibetan Plateau

Abstract: We use receiver functions calculated for data collected by the INDEPTH‐IV seismic array to image the three‐dimensional geometry of the crustal and upper mantle velocity discontinuities beneath northeastern Tibet. Our results indicate an average crustal thickness of 65 to 70 km in northern Tibet. In addition, we observe a 20 km Moho offset beneath the northern margin of the Kunlun Mountains, a 10 km Moho offset across the Jinsha River Suture and gently northward dipping Moho beneath the Qaidam Basin. A region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(134 citation statements)
references
References 118 publications
(146 reference statements)
12
121
0
1
Order By: Relevance
“…Furthermore, we estimated a crustal thickness value for all 72 stations by choosing the center of the large positive velocity gradient at the base of the crust. We found that by choosing the center of the velocity gradient we obtained results roughly consistent with Han et al, 2012. If we chose the base or beginning we obtained generally unrealistic crustal thickness values.…”
Section: Joint Inversion Of Receiver Functions and Surface Wave Dispesupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, we estimated a crustal thickness value for all 72 stations by choosing the center of the large positive velocity gradient at the base of the crust. We found that by choosing the center of the velocity gradient we obtained results roughly consistent with Han et al, 2012. If we chose the base or beginning we obtained generally unrealistic crustal thickness values.…”
Section: Joint Inversion Of Receiver Functions and Surface Wave Dispesupporting
confidence: 70%
“…We compared different velocity models using independent techniques to see which portions of the models are common to all of our models. We used the receiver function work of Han et al (2012) and surface wave phase velocities of Ceylan et al (2013) combined with the global group velocities from Pasyanos (2010) by applying the joint inversion method of Julia, et al (2000). We used Rayleigh wave phase velocities obtained from the two plane wave method and receiver functions calculated using the method of Liggoria and Ammon, 1999.…”
Section: Joint Inversion Of Receiver Functions and Surface Wave Dispementioning
confidence: 99%
“…Based on their model, in the northeastern plateau margin with a gentle topography gradient, the weak mid-tolower crustal materials could escape through the SongpanGanzi terrane toward the southwestern Ordos platform. Our results show that a mid-to-lower crustal LVZ has been observed beneath the northern Qilian orogen, with the highest topography and a thickened crust (∼60 km; Yue et al, 2012) compared to its surrounding regions. However, it has not been found beneath the southern Qilian orogen.…”
Section: Discussionmentioning
confidence: 69%
“…Many studies have been performed in the Tibetan plateau, but most of the geophysical studies of the Tibetan crust and mantle structure to date have focused on the southern Kind et al, 1996;Nelson et al, 1996;Huang et al, 2000;Wei et al, 2001;Wang et al, 2003;Unsworth et al, 2005;Yao et al, 2008;Guo et al, 2009), central (Owens and Zandt, 1997;Kind et al, 2002;Tilmann et al, 2003), and eastern Tibetan plateau , with the primary objectives of understanding the continental collision process and the intrusion of the crustal and mantle materials from the Indian plate into the Eurasian plate. In comparison to other parts of the plateau, fewer seismic investigations have been done in the northeastern Tibetan plateau (e.g., Wittlinger et al, 1996;Zhu and Helmberger, 1998;Vergne et al, 2002Vergne et al, , 2003Karplus et al, 2011Karplus et al, , 2013Yue et al, 2012), which either are localized along linear profiles or focused on the velocity discontinuity structure. In our previous study (Li et al, 2012), we determined that the lowvelocity zone (LVZ) terminated around the east Kunlun fault (KLF) in the northeastern Tibetan plateau.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the crust and the upper mantle in Tibet have obvious zonal characteristics and inhomogeneous distributions of the lower velocity in the crust and the higher velocity in upper mantle [24]. Weak zones occur in the upper crust in the Himalayas, in the middle crust in southern Lhasa, in the middle and lower crust in northern Lhasa, and in the middle and lower crust in Qiangtang and Songpan-Ganzi [25][26][27]. The Indian crust collides with the Tarim Basin at 80 • E and reaches the Bangong Nujiang Suture (BNS) belt at 88 • E (in the west at 90 • E) [11].…”
Section: Geologymentioning
confidence: 99%